2019
DOI: 10.1161/circresaha.118.314048
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Deficiency Leads to Cardiac Dysfunction Accompanied by Cardiomyocyte Dedifferentiation During Pressure Overload

Abstract: The Hippo pathway plays an important role in determining organ size through regulation of cell proliferation and apoptosis. Hippo inactivation and consequent activation of YAP (Yes-associated protein), a transcription cofactor, have been proposed as a strategy to promote myocardial regeneration after myocardial infarction. However, the long-term effects of Hippo deficiency on cardiac function under stress remain unknown. Objective: We investigated the long-term effect of Hippo deficiency on cardiac function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 46 publications
3
102
0
Order By: Relevance
“…S2, C, D, and E). In a recent study (19), we found that YAP is inactivated during the decompensated phase of cardiac hypertrophy. Thus, we sought to determine the functional significance of cardiac YAP activation during the compensated phase of PO.…”
Section: Yap Is Activated In Response To Pomentioning
confidence: 76%
“…S2, C, D, and E). In a recent study (19), we found that YAP is inactivated during the decompensated phase of cardiac hypertrophy. Thus, we sought to determine the functional significance of cardiac YAP activation during the compensated phase of PO.…”
Section: Yap Is Activated In Response To Pomentioning
confidence: 76%
“…Cardiac maturity is central to heart development and disease. It is generally accepted that progressive dedifferentiation of cardiomyocyte, and thus loss of CM identity, is the hallmark molecular event in cardiac hypertrophy 40,41 . By contrast, much less is understood about its microenvironmental setting, especially with regard to how the microenvironment transforms in disease, and subsequently translates into deteriorations in CMs.…”
Section: Discussionmentioning
confidence: 99%
“…Although progresses in myocardial regeneration in Hippo-deficient heart was reported by Tao et al (2016), restoration of overall cardiac function by tuning Hippo-pathway components seems to be a more complex task, which requires additional research and validation. In fact, Ikeda et al (2019) described that long term activation of YAP facilitates the progression of heart failure, in response to pressure overload, in transgenic mice model lacking WW45 Hippo component. Despite homozygous knockout of WW45 (WW45cKO) in Zeng et al, 2003;Allijn et al, 2017 LDL-C, low density lipoprotein-C; CHF, congestive heart failure; Increlex1, mecasermin, a human recombinant IGF-1 analog; IPLEX1, mecasermin rinfabate, a binary protein complex of human recombinant IGF-1 and human recombinant IGBP-3; IGBP-3, insulin-like growth factor binding protein-3; HO-1, heme oxygenase-1; TGFβ, transforming growth factor β; GSK3, glycogen synthase kinase-3.…”
Section: Selective Regulation Of Hippo Pathway To Promote Adult Cardimentioning
confidence: 99%